The impact of service quality on Customer satisfaction of Jordan Insurance Companies - Ahmad Al qudah, Dr Kamal; H. Al-beshtawi, Dr Sulieman; Atallah Al-Tarawneh, Dr. Khaled; Abraheem Shlash Mohammad, Dr. Anber; Adel Abu-Laimon, Amr (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The study aimed to investigate the impact of service quality on Customer satisfaction of Jordan Insurance Companies. The sample for this study consists customers of Jordan insurance companies . These were randomly selected from customers of ALICO insurance company located in in several locations in Jordan. Two hundred and thirty three usable surveys were returned with a response rate of 58.25% . The (SERVQUAL) identifies seven dimensions of service quality: Competence, Credibility, reliability, responsiveness, Assurance, tangibles, Communication.. The study indicates that there was a statistically significant link between seven dimensions service quality and customer satisfaction. The findings of the study have important implications for managers of Jordan Insurance Companies, managers of Jordan Insurance Companies could make Commitment by the offers provided to the customers, so that the advertised offers should match the reality. Great attention to complaints made by customers and considering them seriously by forming specialized committees to respond to these complaints, and W orking on the development of signboards in all centers of the company which include the steps to be followed by customers to receive the service in order to let the customer receives the servicequickly and without errors or delay.